Ладошкины сказки: [0+] / Анна Никольская - Никольская Анна (ИД Мещерякова, 2013)
Экземпляры: ф. 3 (20140604) / Инвентарный номер: 101151 / Цена: 387.53 / Авт.знак: Н 64 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6